Motivasi Host Couchsurfing.Com Area Denpasar Menjadi Pemandu Wisata Traveler - Yulistiana, Eti; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i02.p06, 2018)
Couchsurfing.com is social media which make traveler and local meet in tourist destination. Which is they dont know each other before meet. Share about anything and explore the tourist destination together. Purpose of this research is to know thet motivation of host on couchsurfing.com Denpasar area to be a tour guide for the traveler. This reseacrh used qualitative method. Data collected by observation, in-dept interview and literature study. Sampling technique used purposive sampling. The data analyzed through the stages of editing, classification, coding then interpretation. These results indicate that there is a lot of motivations of  host couchsurfing.com Denpasar to be a tour guide for the traveler. The main motivations isself-actualization, includes practicing foreign language skills, train travel guides skill, improve personal communication skills, understand the character of the travelers, and dream.  The second motivation is esteem needs, prestige and showing hospitality are the part of it. The three last motivation are belongingness and love needs, safety needs, physiological needs.   Keywords : Motivation, Couchsurfing.com, Tour Guide, Traveler